FINANCIAL LITERACY AND USAGE RISK AS DETERMINANTS OF FINTECH PAYMENT INTEREST AMONG GENERATION Z ACCOUNTING STUDENTS - Kadek Dian Jatiwardani; Ni Wayan Risna Swardani; Mertyani Sari Dewi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The rapid development of financial technology (Fintech) in the 5.0 era provides the public with digital access to financial services, offering efficiency, stability, and security. However, these advantages are accompanied by risks such as cyberattacks and data theft, which are further exacerbated by Indonesia’s low level of financial literacy. Despite this, interest in Fintech usage, particularly among Generation Z, continues to grow.   Methods: This study aims to analyze the effect of financial literacy and usage risk on the interest in using Fintech Payment services among Generation Z. The population in this study includes active students of the Accounting Department at Bali State Polytechnic, with a total of 1,501 individuals. A sample of 94 respondents was selected using purposive sampling based on specific criteria: students aged 12–27 years and users of Fintech payment applications such as Shopeepay, Dana, Gopay, or OVO. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Version 26. Results: The results indicate that financial literacy has a positive and significant effect on the interest in using Fintech Payments, while usage risk has a negative and significant effect. These findings suggest that higher financial literacy increases the intention to use Fintech services, whereas higher perceived risk reduces it. It is recommended that Fintech providers enhance user security, and that institutions promote financial education to increase trust and adoption among Generation Z. Keywords: interest in transactions, use of risks, financial literacy, fintech payment.